On the training of MIMO-OFDM channels with least square channel estimation and linear interpolation - Seung Joon Lee, Seung Joon Lee (IEEE communications letters, 2008)
The effect of pilot arrangement is investigated on the performance of trained MIMO-OFDM channels where fading is time-flat in a block of coherence-time duration but frequency-selective. The MIMO-OFDM channel is considered to be trained by using least square channel estimation on pilot subcarriers and by applying linear interpolation on data subcarriers. The achievable rate of such a system is derived employing the generalized mutual information approach. Numerical examples are presented examining the optimal density of pilots in the two-dimensional time-frequency domain.